Le tourisme culturel en Tunisie pendant la période coloniale : Genèse et évolution - Lassaad Dandani (Études Caribéennes)
Since 1961, date of the adoption of the first ten-year development plan, the Tunisian State had bet on tourism in general and essentially on seaside tourism. From this date and for several decades tourism in Tunisia was forged in its seasonal and mass seaside vocation. However, other forms of tourism such as cultural tourism were considered as additional, auxiliary and alternative tourist activities. Indeed, in recent years, contemporary research on the history of tourism in Tunisia has emphasized the idea of the antiquity of cultural tourism. The primary objective of this study is to outline this idea. This contribution tries to understand the modalities of the birth and the evolution of this cultural tourism in Tunisia. We will show in this research that the Tunisian tourism is a cultural tourism par excellence. It was an ancient activity that dates back to the period of the second half of the nineteenth century. Thus, we will try to see if this cultural tourism, such as it is practiced today, is the heir of this activity dating from the colonial period.